2016
DOI: 10.1103/physrevb.93.054422
|View full text |Cite
|
Sign up to set email alerts
|

Tuneability and criticality in a three-dimensional stacked molecular system

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
(52 reference statements)
2
8
0
Order By: Relevance
“…redSince µSR is an excellent probe of weak, local magnetic fields it presents some significant advantages for studying the static and dynamic properties of the defect states.The sensitivity of this technique is a consequence of the fact that muons can implant close to local magnetic moments and experience their local dipolar magnetic fields. The high temperature behaviour through T SP of the muon relaxation has been previously studied [27] and so here, we only focus on the low temperature behaviour. The relaxation at low temperatures is complex as there are many different relaxation mechanisms but at short times one is able to resolve a heavily damped oscillation, a signature of static magnetic moments, on a strongly relaxing background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…redSince µSR is an excellent probe of weak, local magnetic fields it presents some significant advantages for studying the static and dynamic properties of the defect states.The sensitivity of this technique is a consequence of the fact that muons can implant close to local magnetic moments and experience their local dipolar magnetic fields. The high temperature behaviour through T SP of the muon relaxation has been previously studied [27] and so here, we only focus on the low temperature behaviour. The relaxation at low temperatures is complex as there are many different relaxation mechanisms but at short times one is able to resolve a heavily damped oscillation, a signature of static magnetic moments, on a strongly relaxing background.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this transition can be tuned by replacing protons with fluorine atoms on the quinoidal ring of TCNQ using TCNQF 4 (TCNQF 4 = 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane) where a shift in T SP to 160 K is observed [27]. TCNQF 4 is a stronger acceptor than TCNQ as the F atoms can draw an increased amount of electron density into the quinoidal structure.…”
Section: Introductionmentioning
confidence: 99%
“…TCNQ was shown to not only conduct electricity but also able to stablise a radical anion creating an S = 1/2 system that showed interesting magnetic properties. This discovery led to a deluge of research that focused on the novel properties of different compounds [5][6][7][8][9][10][11][12][13] . Substituted TCNQ-based quinodial structures have also shown some interesting optical properties as researchers began to explore cyano-chemistry, most notably mono-substituted TCNQ molecules forming highly polarisable non-linear optical materials 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Simple TCNQ based salts such as K + TCNQ − as well as other alkali metal salts form 1D magnetic systems that exhibit spin-Peierls transitions due to the 1D interactions along these 1D TCNQ anion stacks [17][18][19] . However, recent work has shown that dynamically, this transition is actually 3D and there must be strong coupling of the 1D magnetism with the 3D structural transition 11 . In recent years, TCNQ based compounds have also been shown to exhibit the characteristics of functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…TCNQ is a flat, planer molecule that forms many compounds where interactions along the 1D π-stacked structure can play important/dominant roles, such as is observed with metalinsulator, Peierls and spin-Peierls transitions (SP) [3,4,5,6,7]. In the case of [Fe(III)Cp][TCNQ], both polymorphs show an increase in the magnetic transition as a function of pressure due to increased coupling as intra-and inter-chain distances decrease [8].…”
Section: Introductionmentioning
confidence: 99%